Understanding Implied Meanings In Everyday Language With Pragmatic Theory - Reni Isnaini Pratiwi (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
Pragmatics is a branch of linguistics that studies meaning in the context of language use, especially the context of implied meaning which is not always conveyed directly in everyday language. The purpose of this article is to explain the basic concepts of pragmatic theory and its application in everyday communication. Through this theory, we can understand how implicit meaning plays a role in shaping perceptions, guiding reactions, and influencing relationships between individuals. This article explains how pragmatics can help us understand the deeper meaning of spoken words by considering connotations, presuppositions, and social context. A better understanding of pragmatics allows individuals to communicate more effectively and understand hidden messages in conversations. We hope this article provides readers with new insights into the importance of pragmatics in everyday social interactions and how this theory can help overcome misunderstandings that are often caused by different interpretations.